Technology Acceptance of Battery Electric Vehicle as Mediator from Online Community to Customer Citizenship Behavior - อัครมิ่งมงคล, วรดิษฐ์ (Pathumthani University Academic Journal, 2020)
The purpose of this study was to investigate the customer citizenship behavior (CCB) from online communities by unified theory of acceptance and use of technology (UTAUT) as a mediator both of direct and indirect effects in battery electric vehicle industry. An online survey study with 400 respondents from online community members. Statistics used for data analysis were Frequency, percentage, average, standard deviation and structural equation model analysis. The results showed that the most consumers were males, aged 24-40 years, single-level, bachelor degree, entrepreneur, earning less than 30,000 baths per month. The hypothesis testing showed that online community has effect on the UTAUT and only the in-role behavior from CCB. UTAUT has a mediating role in converting the effects of enhanced relationships in online community to CCB and types of value were significant statistical confidence level of 0.05